A new species of Psychomyia (Trichoptera, Psychomyiidae) from China - Tao, Zhulin; Qiu, Shuang (Zootaxa, 2024)
The male and female of a new species of the genus Psychomyia Latreille 1829, Psychomyia tahmanica sp. nov., is described based on morphological characters and molecular data (COI). Images of the adults and genitalia are provided.